Ultrasensitive detection of genomic DNA from apple leaf tissues, using surface-enhanced Raman scattering. Issue 1 (2011) - Muntean Muntean, Cristina M. Cristina M.; Leopold Leopold, Nicolae Nicolae; Halmagyi Halmagyi, Adela Adela; Valimareanu Valimareanu, Sergiu Sergiu
Abstract : Ultrasensitive detection of nucleic acids is demonstrated through exploiting the effect of surface-enhanced Raman scattering (SERS). In this work the SERS spectra of eight genomic DNAs from leaves of apple trees grown in the field ( Malus domestica Borkh., Fam. Rosaceae, cultivars. Florina, Idared, Rebra, Goldrush, Romus 3, Romus 4 and the rootstocks M9 and M26) have been analyzed in the wavenumber range 200–1800 cm –1 . SERS signatures, spectroscopic band assignments and structural interpretations of these plant genomic DNAs are reported. SERS spectra of nucleic acids are compared here with caution, because these signals are time-dependent and are strongly influenced by DNA amount in the measured sample volume. Similarities of the SERS spectra of genomic DNAs extracted from apple leaves of Goldrush, Rebra and Florina cultivars, respectively, have been detected. Besides, the SERS spectra, corresponding to DNA from M9, Romus 4 and M26, leaves, respectively, show similar features and well resolved bands. Based on this work, specific plant DNA-ligand interactions or DNA structural changes induced by plant stress conditions associated with their natural environment, might be further investigated using surface-enhanced Raman spectroscopy.